The Effect of Capping Agents on the Structural and Magnetic Properties of Cobalt Ferrite Nanoparticles - Casagrande-Denardin, J (Springer New York LLC, 2018)
Microwave-assisted co-precipitation method was adopted to analyze the effect of polyethylene glycol (PEG) and urea concentrations on the properties of cobalt ferrite nanoparticles (NPs). The average crystallite size of single phase cubic spinel cobalt ferrite NPs was controlled within 10–14 nm with the effect of PEG, urea and the combination of them. The transmission electron micrographs revealed that the morphology of cobalt ferrites was not significantly influenced by the different concentration of capping agents but almost uniform morphology with nearly narrow size distribution was obtained. The interaction of PEG and urea molecules on the surface of nanoparticles was mediated through –OH hydroxyl group affected the crystal growth rate. The possible interaction mechanism was proposed with the help of IR vibrational spectra. All the samples exhibited ferromagnetism at room temperature and it was found that the capping agents showed an effect on the magnetic properties. The maximum saturation magnetization of 58 emu/g was achieved when the urea of 60 mg was used and the maximum coercivity of 311 Oe was attained when the mixture of PEG (40 mg) and urea (20 mg) were used. Ultrafine and hydrophilic cobalt ferrite NPs that showed appreciable magnetic properties obtained in the present experimental procedure would be of great interest in various biomedical applications. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.